2017
DOI: 10.1186/s12879-017-2321-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Smear-Positive Pulmonary Tuberculosis in the Hetosa District of Arsi Zone, Oromia Regional State of Central Ethiopia

Abstract: BackgroundThe real burden of smear-positive (PTB+) and bacteriologically confirmed tuberculosis (BCTB) in Ethiopia is not known. Thus, the aim of this community-based study was to measure the prevalence and incidence of tuberculosis in the Hetosa District of Oromia Region, Ethiopia.MethodsFirst, a population-based cross-sectional survey was conducted on a total of 33,073 individuals aged ≥ 15 years to determine the prevalence of PTB+ and BCTB cases. Then, in order to determine the incidence, a prospective foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 36 publications
5
29
6
Order By: Relevance
“…16 This might be due to differences in population and study layout (a prospective study was conducted on patients with type 2 DM) in north India, which had relatively decent insulin secretion and glycemic control that prevented the development of complications and coinfections compared to type 1 DM. Conversely, our finding is much lower than the TB incidence reported in Australia (5.8 per 100 PYs) and Ethiopia (Black Lion [ 3.8 per 100PYs] 17 and Dessie [6.2 per 100PYs] referral hospitals 18 ). In the same way, these variations among studies could be explained in part by differences in sample size, study settings, followup periods, and sociodemographic characteristics of study participants.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…16 This might be due to differences in population and study layout (a prospective study was conducted on patients with type 2 DM) in north India, which had relatively decent insulin secretion and glycemic control that prevented the development of complications and coinfections compared to type 1 DM. Conversely, our finding is much lower than the TB incidence reported in Australia (5.8 per 100 PYs) and Ethiopia (Black Lion [ 3.8 per 100PYs] 17 and Dessie [6.2 per 100PYs] referral hospitals 18 ). In the same way, these variations among studies could be explained in part by differences in sample size, study settings, followup periods, and sociodemographic characteristics of study participants.…”
Section: Discussioncontrasting
confidence: 88%
“…Accordingly, patients with a history of TB were 12 times as likely to develop TB than their counter parts (incidence-rate ratio 12, (95% CI 3-39); P=0.01), which is consistent with a study conducted in Australia 20 and studies in Ethiopia. 17,18,22 In addition, our study demonstrated that patients with BMI ≥18.5 kg/m 2 were at higher risk of TB than their counterparts (BMI <18.5 kg/m 2 , incidence-rate ratio 0.34, 95% CI 0.14-0.80; P=0.03), which aligns with previous studies conducted in southeastern Amhara, 26 Ethiopia (systematic review), 22 Egypt, 27 the US, 23,28 and China (adjusted HR 0.89, 95% CI 0.76-1.03). 25 Conversely, this study's findings contradict those of the study conducted in Ethiopia at Black Lion hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of laboratory-confirmed TB was 139 per 100 000 population, much lower than the national prevalence of 277 per 100 000 population (95% CI 208-347) (Kebede et al, 2014). The prevalence of smearpositive pulmonary TB was also lower than in several previous studies in Ethiopia, including the national prevalence survey (Kebede et al, 2014;Berhe et al, 2013;Hamusse et al, 2017;Shargie et al, 2006b;Yimer et al, 2009;Tadesse et al, 2011), but higher than a report from southwest Ethiopia (Deribew et al, 2012). Direct comparison is difficult because of differences in study methodology, population, and time.…”
Section: Number Of Householdsmentioning
confidence: 58%
“…The prevalence of smear-positive pulmonary TB was 108 per 100 000 per population according to a national populationbased TB survey conducted from October 2010 to June 2011, in which the vast majority of those identified were newly diagnosed cases that had not been captured by the control programme and most (55%) were among the younger age groups (15-34 years) (Kebede et al, 2014). Additional studies across various rural settings in Ethiopia have found a range of smear-positive pulmonary TB prevalence rates (from 30 to 174 per 100 000 population) suggesting that disease epidemiology varies across different geographical locations of the country (Berhe et al, 2013;Hamusse et al, 2017;Shargie et al, 2006b;Deribew et al, 2012;Yimer et al, 2009;Tadesse et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This could be one of the reasons of TCPS progress. The access of TB care providers to international TB programs in their local language could remove extra cost in the fields of trial and error and planning alternative programs [28]. The TCPS screened whole Sistan area except Zabol city (the biggest city of this area) and it could be one of TB spread causes.…”
Section: Discussionmentioning
confidence: 99%